2020
DOI: 10.1111/jpi.12631
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin alleviates vascular calcification and ageing through exosomal miR‐204/miR‐211 cluster in a paracrine manner

Abstract: In the elderly with atherosclerosis, hypertension and diabetes, vascular calcification and ageing are ubiquitous. Melatonin (MT) has been demonstrated to impact the cardiovascular system. In this study, we have shown that MT alleviates vascular calcification and ageing, and the underlying mechanism involved. We found that both osteogenic differentiation and senescence of vascular smooth muscle cells (VSMCs) were attenuated by MT in a MT membrane receptor‐dependent manner. Moreover, exosomes isolated from VSMCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(83 citation statements)
references
References 53 publications
1
82
0
Order By: Relevance
“…Through interference with ATS progression, melatonin also possibly contributes to slower development of ischemic heart disease [ 127 ]. Moreover, it inhibits calcium accumulation, leucocyte infiltration, and endothelial damage [ 167 , 168 ]. In addition, it has antithrombotic effects through a reduction in platelet reactivity [ 129 ].…”
Section: Melatonin’s Role In Programming Adult Cardiovascular Homementioning
confidence: 99%
“…Through interference with ATS progression, melatonin also possibly contributes to slower development of ischemic heart disease [ 127 ]. Moreover, it inhibits calcium accumulation, leucocyte infiltration, and endothelial damage [ 167 , 168 ]. In addition, it has antithrombotic effects through a reduction in platelet reactivity [ 129 ].…”
Section: Melatonin’s Role In Programming Adult Cardiovascular Homementioning
confidence: 99%
“…For instance Li et al reported that exosomes derived from high glucose induced endothelial cells could carry versican protein to accelerate VSMCs calci cation [9]. Our previous study demonstrated that melatonin alleviated vascular calci cation through an exosomal miR-204/miR-211 cluster in a paracrine manner [11]. However, the role and mechanism of exosomes in regulating vascular calci cation in patients with ESRD is not very clear.…”
Section: Introductionmentioning
confidence: 97%
“…Exosomes play a role in cardiovascular system as well. Our present study investigated that exosomes derived from melatonin-treated vascular smooth muscle cells could mitigate vascular calcification and aging through an exosomal miR-204/miR-211 cluste [31]. Cheng et al proposed a mechanism whereby miRNAs enveloped in impaired myocardium-derived exosomes can be selectively transferred into bone marrow cells to mobilise progenitor cell migration to lesions, promoting heart tissue repair [30].…”
Section: E Function Of Exosomesmentioning
confidence: 91%